CaverDock: a molecular docking-based tool to analyse ligand transport through protein tunnels and channels - Vavra, Ondrej; Filipovic, Jiri; Plhak, Jan; Bednar, David; Marques, Sergio M; Brezovsky, Jan; Stourac, Jan; Matyska, Ludek; Damborsky, Jiri (Bioinformatics (Oxford, England), 2019)
MOTIVATION: Protein tunnels and channels are key transport pathways that allow ligands to pass between proteins' external and internal environments. These functionally important structural features warrant detailed attention. It is difficult to study the ligand binding and unbinding processes experimentally, while molecular dynamics simulations can be time-consuming and computationally demanding. RESULTS: CaverDock is a new software tool for analysing the ligand passage through the biomolecules. The method uses the optimized docking algorithm of AutoDock Vina for ligand placement docking and implements a parallel heuristic algorithm to search the space of possible trajectories. The duration of the simulations takes from minutes to a few hours. Here we describe the implementation of the method and demonstrate CaverDock's usability by: (i) comparison of the results with other available tools, (ii) determination of the robustness with large ensembles of ligands and (iii) the analysis and comparison of the ligand trajectories in engineered tunnels. Thorough testing confirms that CaverDock is applicable for the fast analysis of ligand binding and unbinding in fundamental enzymology and protein engineering. AVAILABILITY AND IMPLEMENTATION: User guide and binaries for Ubuntu are freely available for non-commercial use at https://loschmidt.chemi.muni.cz/caverdock/. The web implementation is available at https://loschmidt.chemi.muni.cz/caverweb/. The source code is available upon request. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Algorithms; Software; simulace molekulového dockingu; proteiny; Binding Sites; Ligands; Proteins; software; vazebná místa; ligandy; Molecular Docking Simulation; algoritmy